Ku‐ and Ka‐Band Polarimetric Radar Waveforms and Snow Depth Estimation Over Multi‐Year Antarctic Sea Ice in the Weddell Sea - Rosemary Willatt; Robbie Mallett; Julienne Stroeve; Jeremy Wilkinson; Vishnu Nandan; Thomas Newman (Geophysical Research Letters, 2025)
Abstract Antarctic sea ice has seen recent rapid declines in extent, but it remains unclear whether this is accompanied by thinning. Due to the relative abundance and complexity of overlying snow on sea ice, radar altimetry methods routinely deployed for sea ice thickness estimation in the Arctic are difficult to apply in Antarctica. We present nadir‐looking radar waveforms from the first deployment of the KuKa surface‐based radar on Antarctic sea ice, specifically multi‐year sea ice in the Weddell Sea marginal ice zone with a thick snow cover. Coincident snow pits revealed thick layers of snow which were exposed to the summer melt season and superimposed ice. Our instrument detects only very small amount of co‐polarized radar backscatter from the sea ice surface, suggesting that conventional satellite altimeters may not always range to this interface. However, polarimetric snow depth determination performs well, with r2 of 0.76 between measured and KuKa‐estimated snow depths.